(untitled) (Revista Electrónica Calidad en la Educación Superior, 2017)
One of the great challenges that the Ministry of Public Education (MEP) has in Costa Rica is to improve the quality of teaching chemistry at the secondary level and reduce the gap between scientific and academic schools. The Universidad Estatal a Distancia (UNED), as a higher education institution worried about this problem created a diagnostic-level plan in chemistry to establish basic knowledge of this subject for students entering the Industrial Engineering career, this plan consisted of Two stages: The first stage was carried out between 2013 and 2014 where a diagnostic test was carried out, which was applied to scientific and academic colleges that attended the diversified cycle and to students who wanted to enter the industrial engineering career. The second stage was to create a leveler course in chemistry, in order for first-year students to acquire basic knowledge to undertake university courses in General Chemistry I, which has been taught since 2014 to date by the UNED. This paper presents the experience of the Chair of Chemical Sciences in the design and implementation of the diagnostic test and the first results obtained from the leveling chemistry course as a strategy to improve the academic performance of students entering the UNED.